A Marketing Mix Model for Pharmaceutical Industry — A Pakistani Perspective - Sattar, Irfan; Maqsood, Azra (JISR management and social sciences & economics, 2003)
This study attempts to create a model, which explain the relationship between different elements of marketing mix with special reference to pharmaceutical industry in Pakistan. All the four P’s have been discussed at length to understand the unique characteristics of pharmaceutical marketing mix, and the differences they possess as compared to general marketing. This study forms the basis of developing more detailed text for pharmaceutical marketing.